The Effect of Peer Feedback and Teacher Feedback on The Improvement of Imla’ Errors and The Psychological Attitudes of Eighth-Grade Students at Mts Al-Fath Klaten - Nirmala Luthfia Hamaz; Oktavia Dwi Lestari; Muhammad Subhi; Tulus Musthofa (Abjadia : International Journal of Education, 2026)
This study aims to examine the effect of peer feedback and teacher feedback on the improvement of imlā’ errors and the psychological attitudes of eighth-grade students at MTs Al-Fath Klaten. The research employed a quasi-experimental method with a pretest–posttest non-equivalent control group design. The participants involved two intact classes of 13 students each, purposively selected as the experimental group (peer feedback) and the control group (teacher feedback). Data were collected through tests to measure students’ imlā’ errors and questionnaires to assess changes in their psychological attitudes. The results indicate that both peer feedback and teacher feedback effectively improve the accuracy of Arabic letter writing, harakat usage, and word structure. In addition, both feedback strategies positively enhance students’ motivation, self-confidence, and engagement in writing activities. These findings confirm that the integration of peer feedback and teacher feedback can foster a more collaborative, effective, and psychologically supportive learning process in imlā’ instruction.